9.1: Invited Paper: Shape discrimination ability and disability glare in orthokeratology children. (4th October 2019) - Jiang, Jun; Su, Binbin; Zhou, Lin; Zhang, Bin; Fan, Lv
Abstract : Purpose: A commonly reported complaint in orthokeratology treatment is the disturbing glare whose mechanism remains unclear. In this study, we measured the changes in shape discrimination ability, with and without the presence of transient disability glare, during the first month in children who underwent orthokeratology treatment. Method: Forty‐nine eyes from 49 children (age: 11.49±2.02 years) with mean spherical equivalent refractive error ‐3.23±1.09D were included into this prospective study. Radial frequency (RF) patterns were used as the visual stimuli. Shape discrimination thresholds (SDT), with and without glare, were measured using a 2‐down‐1‐up staircase procedure. SDTglare was defined as the difference between the SDTs with and without the presence of glare. Measurements were done at baseline with frame spectacles, and days 7 and 30 of after treatment with naked eyes. Result: No statistically significant differences were observed between the SDTs without glare obtained at baseline and 1 week and 1 month after orthokeratology lens wear (P > 0.05). With transient glare, SDTs in all subjects were significantly higher than SDTs without glare (P < 0.05). SDTs with glare on day 7 and day 30 were significantly lower than baseline (P < 0.05). Compared with baseline, SDTglare significantly decreased at 1 week and 1 month after orthokeratology lens wear (P < 0.05). Conclusion: While SDT without glare was stable following orthokeratology treatment, SDT with glare decreased during the first month of treatment. This short‐term reduction in SDT may be the combined effect of spectacle removal, subtle changes in cornea optical quality, and the neural adaptation.